Structure of 2-{2-[3-methyl-3-(2,4,6-trimethylphenyl)cyclobutyl]-2-oxoethyl}isoindole-1,3-dione - Sari, U; Yilmaz, I; Güven, K; Çukurovali, A; Aksoy, I (Springer/Plenum Publishers, 2004)
2-{2-[3-Methyl- 3-(2,4,6-trimethylphenyl) cyclobutyl]-2-oxoethyl} isoindole-1,3-dione (C-24 H25NO3) was synthesized, and its crystal structure was determined by X-ray crystallographic techniques. The compound crystallizes in the triclinic space group P-1, with unit cell parameters: a = 14.109(9) Angstrom, b = 14.130( 8) Angstrom, c = 12.152( 6) Angstrom, a = 105.62( 5)degrees, beta = 113.75( 4)degrees, gamma = 98.78(5)degrees, V = 2039.8(19) Angstrom(3), D-c = 1.223 g/cm(3), and Z = 4. The crystal structure has two crystallographically independent molecules, I and II. These molecules are held together by weak intermolecular C-H ... O interactions, forming a continuous chain. The dihedral angles between the N-substituted phthalimide moiety and cyclobutane ring in molecules I and II are 60.37(14) and 68.18(18)degrees, respectively.
Keywords: X-ray; N-sustituted phthalimides; crystal structure